Characteristics of UHF Propagation Channels Due to the Impact of Vegetation on WSN in The Tropical Forests - Kurniawati, Indah; Akbar, Ridho; Astomo, Reynanda Bagus (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2025)
The use of wireless communication in a wireless sensor network, especially in smart gardens, requires information about the amount of attenuation caused by vegetation. Therefore, measurements were made of the Received Signal Strength Indicator (RSSI) received by the XBee S2C device in the Bamboo Forest area, Surabaya, for several different lengths of vegetation depth and antenna height. From the measurement results, it is known that there is no significant difference between RSSI for antenna heights of 1 m and 2 m, while better RSSI is obtained for antennas with a height of 3 m. The antenna used is a vertical monopole antenna for the 2.4 GHz frequency. This is because, at an antenna height of 3 m, the number of vegetation that becomes obstacles is less than that of antennas of 1 m and 2 m. From the measurement results, it is also known that with this antenna height, data packets can be received up to a vegetation depth of 80 m. Then, the attenuation resulting from the calculation shows that the resulting trend is in accordance with the attenuation trend with the Weissberger, ITU-R, and FITU-R models but with higher values. Differences in measurement methods, locations, obstacles, and different climates and weather can cause this. To predict attenuation at a certain vegetation depth distance, based on the results of the attenuation calculation, a linear equation for calculating attenuation as a function of distance is created of the attenuation calculation, a linear equation for calculating attenuation as a function of distance is created.